2020
DOI: 10.1021/acs.jnatprod.9b00647
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial 9-Methoxystrobilurins, Oudemansins, and Related Polyketides from Cultures of Basidiomycete Favolaschia Species

Abstract: Fourteen new compounds, oudemansins 1–4, oudemansinols 5–7, favolasins 8–10, favolasinin (12), polyketides 13–15, and (R,E)-2,4-dimethyl-5-phenyl-4-pentene-2,3-diol (16), together with nine known compounds were isolated from the basidiomycete fungus Favolaschia sp. BCC 18686. Two new compounds, favolasin E (11) and 9-oxostrobilurin E (17), were isolated from the closely related organism Favolaschia calocera BCC 36684 along with nine β-methoxyacrylate-type derivatives. Compounds in the class of oudemansins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 26 publications
3
30
0
Order By: Relevance
“…In addition, the acetonide derivative of 8 was used to produce 8a (Figure ). The NOESY correlations of 8a indicated that the protons connected to C-4, C-5, and C-9 are α-oriented. The NOESY correlation of H-8/H-2 revealed the β-orientation of H-2.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the acetonide derivative of 8 was used to produce 8a (Figure ). The NOESY correlations of 8a indicated that the protons connected to C-4, C-5, and C-9 are α-oriented. The NOESY correlation of H-8/H-2 revealed the β-orientation of H-2.…”
Section: Resultsmentioning
confidence: 99%
“…9 The method was also applied successfully with the natural product (5S,6R,Z)-3-methyl-6-phenyl-3-hexene-1,5,6-triol. 10 A good-quality crystal of (R)-THENA-(2S,3S)-butane-2,3-diol was collected. The X-ray diffraction analysis clearly showed the THENA plane and the deshielding zone which affected the chemical shift of the methyl protons of the diol part.…”
Section: Cluster Synlettmentioning
confidence: 99%
“…9 The method was also applied successfully with the natural product (5 S ,6 R , Z )-3-methyl-6-phenyl-3- hexene-1,5,6-triol. 10…”
mentioning
confidence: 99%
“…manipularis. Kornsakulkarn et al (2019) reported that Favolaschia sp. BCC 1868 and F. Calocera BCC 36684 isolates have 9methoxystrobilurins G,K compounds as antimalarial drugs.…”
Section: Favolaschia Spmentioning
confidence: 99%